MENGEMBANGKAN PELAYANAN BERBASIS SISTEM OTOMASI DI PERPUSTAKAAN PERGURUAN TINGGI - Chairul Ihsan; Antonius Totok Priyadi (Universitas Tanjungpura, 2020)
AbstractThe method that used on this last assigment are descriptive method with qualitative approach. Also the data that provided on this article was achieved from observation,interviews,and documentation. The result from this research are developing a services based on automated system over stmik pontianak library was really needed,because this services will help every library user to find the appropriate subjects that their needed. According the case writer can ensure that automated system was very important and useful due to improve the library function and more of tha this system can also help librarians to give their services more fast and efficient so the user can be satisfiedKeyword: Services, System, Otomation, University Library